PENGARUH THIN CAPITALIZATION DAN CAPITAL INTENSITY TERHADAP TAX AGGRESIVENESS DENGAN SALES GROWTH SEBAGAI VARIABEL PEMODERASI - Sheily, Debora; Soetardjo, Mulyadi Noto (Jurnal Penelitian Akuntansi (JPA), 2024)
The research aims to determine and analyze the influence of thin capitalization and capital intensity towards tax aggresiveness with sales growth as a moderating variable in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. This research uses 205 research sample data. The measurement of tax aggresiveness uses Effective Tax Rate meanwhile the measurement of thin capitalization and capital intensity uses debt to equity ration and total fixed assets to total assets ratio. Using linear regression analysis method this research shows that thin capitalization and capital intensity can significantly negatively influence tax aggresiveness. Meanwhile, sales growth can strengthen the negative influence of thin capitalization on tax aggressiveness but can not moderate the negative influence of capital intensity on tax aggressiveness.